ANALYSIS OF THE UNDERSTANDING OF TOLERANCE BETWEEN RELIGIONS IN TOURISM MAHA VIHARA MAJAPAHIT, MOJOKERTO - Egivia Rivaluna Rifiatul Aini; Ela Choirunisa; Tasya Febrianti; Alfianita; Dewi Puspa Arum; Chrystia Aji Putra; A. Muammar Alawi (JOURNAL OF HUMANITIES AND SOCIAL STUDIES, 2023)
This article discusses the analysis of religious tolerance and harmony in Majapahit Maha Vihara Tourism, a Buddhist place of worship located in Bejijong Village, Trowulan District, Mojokerto Regency, East Java. This research aims to examine the understanding of religious tolerance in the interaction of the community in the tourist area as well as the visitors. This research uses a qualitative approach. The techniques used in data collection are interviews and literature studies. This research produces: First, the attitude of tolerance carried out by the community around the tourist attractions and visitors to Maha Vihara Majapahit. Second, the positive contributions made by the community around the tourist area. This article provides insight into the important role of places of worship in strengthening attitudes of tolerance between religious communities and making a positive contribution in realizing a pluralistic society.